Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ajpath.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Vorinostat (SAHA) Suppresses IL-1β–Induced Matrix Metallopeptidase-13 Expression by Inhibiting IL-6 in Osteoarthritis Chondrocyte

Abstract: Osteoarthritis (OA) is the most common whole-joint disease and is characterized by progressive loss of the cartilage matrix. Matrix metallopeptidase-13 (MMP-13) is a highly active and an abundantly expressed protease in OA cartilage and chondrocytes and degrades type II collagen and proteoglycans. We investigated the mechanism of MMP-13 suppression by histone deacetylase inhibitor vorinostat (SAHA). OA chondrocytes were obtained from knee cartilage after enzymatic digestion and treated with IL-1b in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Interestingly, the expression levels of this protein were higher in OA cartilage than in normal tissue [ 42 ], as also confirmed by our data. Furthermore, the inhibition of HDAC-4 by Vorinostat (SAHA) significantly reduced IL-1β/IL-6-induced expression of catabolic genes, especially MMP-13 , in human OA cartilage explants and chondrocytes [ 43 ]. Following in vitro transfection studies, HDAC-4 was identified as a direct target gene of miR-365 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression levels of this protein were higher in OA cartilage than in normal tissue [ 42 ], as also confirmed by our data. Furthermore, the inhibition of HDAC-4 by Vorinostat (SAHA) significantly reduced IL-1β/IL-6-induced expression of catabolic genes, especially MMP-13 , in human OA cartilage explants and chondrocytes [ 43 ]. Following in vitro transfection studies, HDAC-4 was identified as a direct target gene of miR-365 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a class of proinflammatory cytokines, interleukins (ILs) have been shown to play critical roles in a wide range of chronic inflammatory diseases including OA. Of these, the expression of IL-6, which is upregulated by oxidative stress and ROS, has been shown to be involved in the pathogenesis of OA [14,28]. Furthermore, this response is mediated through activation of the NF-jB signaling pathway [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Vorinostat was first approved in 2006 by the US Food and Drug Administration for the treatment of cutaneous manifestations in patients with cutaneous T-cell lymphoma in whom other treatments have failed. The study by Makki and Haqqi, 2 showing vorinostat-mediated suppression of MMP-13 through inhibition of IL-6 in chondrocytes, suggests the potential of vorinostat as a therapeutic agent for the management of OA.…”
Section: Potential Use Of Hdac Inhibitors In Oa Managementmentioning
confidence: 99%
“…As the first report suggesting HDAC inhibitor vorinostat as a suppressor of IL-6einduced signaling events in OA, this study has a potential of opening new avenues in OA management. 2 Indeed, hyperacetylation of histone proteins up-regulates cell cycle inhibitors (p21 Cip1 , p27 Kip1 , p16 INK4 ), represses inflammatory cytokines (IL-1, IL-8, tumor necrosis factor-a, TGF-b), and down-regulates immune stimulators (IL-6, IL-10, CD154). 13 Furthermore, aberrant HDAC activity has been linked to a wide variety of pathological conditions.…”
Section: Potential Use Of Hdac Inhibitors In Oa Managementmentioning
confidence: 99%
See 1 more Smart Citation